1989
DOI: 10.1002/yea.320050106
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and analysis of the Kluyveromyces lactis TRP1 gene: A chromosomal locus flanked by genes encoding inorganic pyrophosphatase and histone H3

Abstract: The TRP1 gene of the yeast Kluyveromyces lactis has been cloned from a genomic library by complementation of the Saccharomyces cerevisiae trp1-289 mutation. The gene was located within the clone by transposon mutagenesis and the coding region identified by DNA sequencing. This has indicated that K. lactis TRP1 encodes a 210-amino acid polypeptide which shows 53% identity to the homologous S. cerevisiae protein. The K. lactis TRP1 gene has been disrupted by substituting the S. cerevisiae URA3 gene for a large p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(49 citation statements)
references
References 43 publications
5
44
0
Order By: Relevance
“…Chromosomal DNA was isolated and used in Southern-blot analysis, which revealed that a high percentage of the phleomycinresistant transformants contained the disruption fragment integrated at non-homologous positions in the genome (data not shown). This phenomenon of a high integration at non-homologous sites in K. lactis has also been observed by others (Stark and Milner 1989;Mulder et al 1994). Apparently, the process of homologous recombination in K. Iactis is less sequence-specific than it is in S. cerevisiae.…”
Section: The Kicpf1 Gene Is Essential For Cell Viability In K Laetissupporting
confidence: 80%
See 1 more Smart Citation
“…Chromosomal DNA was isolated and used in Southern-blot analysis, which revealed that a high percentage of the phleomycinresistant transformants contained the disruption fragment integrated at non-homologous positions in the genome (data not shown). This phenomenon of a high integration at non-homologous sites in K. lactis has also been observed by others (Stark and Milner 1989;Mulder et al 1994). Apparently, the process of homologous recombination in K. Iactis is less sequence-specific than it is in S. cerevisiae.…”
Section: The Kicpf1 Gene Is Essential For Cell Viability In K Laetissupporting
confidence: 80%
“…This yeast is related to S. cerevisiae and generally shows a high conservation of both sequence and function within structural genes (Stark and Milner 1989;Bergkamp-Steffens et al 1992), but tends to display an informative divergence of both features in regulatory factors, e.g., TFIIB (Na and Hampsey 1993), ABF1 (Gonqalves et al 1992), REB 1 (Morrow et al 1993) and HAP3 (Mulder et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…(A) Leftmap of VDE-reporter inserts at HIS4, showing digests used to detect recombination intermediates and products. One parent (P1) contains ARG4 sequences with a VDE-recognition site (arg4-VRS), flanked by an nourseothricin-resistance module [natMX, (Goldstein and McCusker, 1999)] and the Kluyveromyces lactis TRP1 gene [KlTRP1, (Stark and Milner, 1989)]; the other parent (P2) contains ARG4 sequences with a mutant, uncuttable VRS site [arg4-VRS103, (Nogami et al, 2002) flanked by URA3 and pBR322 sequences. Digestion with HindIII (H) and VDE (V) allows detection of crossovers (CO1 and CO2) and noncrossovers (NCO); digestion with HindIII alone allows detection of crossovers and DSBs.…”
Section: Resultsmentioning
confidence: 99%
“…Tyr 139, which forms a hydrogen bond to the anion in the present structure, can serve as a proton donor for this Pi. It is difficult to be certain Amino acid sequences have been determined for soluble PPases from Saccharomyces cerevisiae (cytoplasmic, Kolakowski et al, 1988; mitochondrial, Lundin et al, IWI), Schizosaccharomyces pombe (Kawasaki et al, 1990), Kluyveromyces lactis (Stark & Milner, 1989), bovine retina (Yang & Wensel, 1992), Arabidopsk thaliana (Kieber & Signer, 1991), E. coli (Lahti et al, 1988), Thermoplasma acidophilum (Richter & Schafer, 1992), thermophilic bacterium PS-3 (Ichiba et al, 1990), Bacillusstearothermophilus and 7: thermophilus (Ishii K, Shibuya K, Kaji H, Satoh T, Teplyakov A, Obmolova G , Kuranova I, Samejima T, manuscript in prep.). Their alignment clearly shows 2 distinct groups with much higher similarity inside the groups than between them.…”
Section: Active Center and Catalytic Mechanismmentioning
confidence: 99%